Bioremediation of Nickel and Lead contaminated soil by Vica faba L. plant and AM fungi Glomus mosseae (Baghdad Science Journal, 2015)
This study is conducted to determine the activity of plant Vica faba and two isolated from arbuscular mycorrhizae fungi (A,B) in bioremediation of soil pollution by Nickel and Lead elements in north and south of Baghdad city. The results showed that the average of soil pollution by Nickel and Lead elements in north of Baghdad was less than the average of soil pollution in the south of Baghdad which recorded 29.0,9.0PPm and 42.0, 25.0PPm respectively. The results show that the isolate A from the polluted soil is more active from isolate B which isolate from unpolluted soil for bioremediation. Vica faba recorded more in accumulate the Lead element in shoot system which was 19.65PPm and in root system was 27.2PPm and for Nickel element 24.65, 27.55PPm in shoot and root respectively.